Commitment and control: Teamwork as management tool in a welfare state bureaucracy (Sociologisk Forskning, 2021)
Teamwork is a well-known management technique for eliciting commitment and exerting control in private companies. However, less is known about how teamwork operates as a management tool in welfare state bureaucracies. Tying critical management and street-level bureaucracy studies, this article explores teamwork as a key component in the normative control of street-level bureaucrats within the Swedish Social Insurance Agency. Based on extensive ethnographic research, the analysis demonstrates how teamwork functions as a subtle steering device in public management. The analysis identifies teams as: a) performative tools; b) cushioning structures; and c) “moral corsets” on caseworkers. By the seamless linking of vertical and horizontal governance mechanisms, teamwork was instrumental in achieving organizational targets, thereby changing the nature of casework and reducing caseworkers’ discretion. The findings call for more research on the normative shaping of caseworkers under new forms of public management.
Keywords: caseworker; institutional ethnography; normative control; street-level bureaucracy; teamwork